Inclusive design to support independent living of elderly citizens in Saudi Arabia - Alfetais, Aysha Mnea A. (2024)
Globally, the elderly suffer an increased number of falls in their homes. Notably, the Kingdom of Saudi Arabia has a high percentage of elderly falls due to inadequate home interior design for independent living. However, the Ministry of Housing is currently unable to fulfil these housing requirements. In this study, the researcher aimed to document best practices in interior design that support independent living for the elderly. The study looks into the current challenges that elderly people face in interior home design. Accordingly, the study develops and formulates building codes that support independent living for the elderly to reduce falls among this population. A qualitative method based on a case-study approach was employed, whereby a total of 12 informants, including 10 elderly and two professionals from Saudi Building Codes, were purposefully and snowball-identified. Data are collected through thematic review, in-depth semi-structured interviews, and physical observations of the interior design of existing elderly homes. The data obtained from the review and interview were analysed based on a thematic analysis matrix using Atlas.ti software. The thematic review revealed that the integration of inclusive principles in interior design plays a crucial role in promoting independent living for elderly citizens. It is understood that accessibility, flexibility, safety, environmental comfort, and social interaction have been considered and incorporated as requirements in interior design houses in most countries across the globe. The result further revealed that most of the elderly faced obstacles related to the lack of an elevator for easier movement in the building, and the main challenges that increased the risk of falling and leading to serious injury among the elderly in their independent living in Saudi homes were due to slippery floors and physical barriers. The findings suggest some important changes to the existing residential codes for future practice to reduce the high rate of falls among the elderly. First, the codes formulated, which include flexibility 1029.14.1, social interaction 1029.5, and accessibility codes 1105.1.8, should be considered by the Saudi Building Code Committee, the Saudi Council of Engineers, and the Ministry of Housing in providing homes to the elderly. The findings of the study will therefore be helpful to policymakers in understanding the issues of poor housing that affect elderly independent living. Therefore, the findings of the study contribute to improved knowledge of the framework of best practices for interior design that provide an inclusive strategy to support independent living for the elderly.